Detection of the effect of the current water crisis on the reduction of the water surface of the Po River, Italy - Nascimento, Eduardo Soares; Galo, Maria de Lourdes Bueno Trindade; Benini, Sandra Medina (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
Italy has been dealing with a major environmental problem in recent times – the water crisis. It is known that this environmental problem can be caused by droughts, lack of rain, and pollution. In July 2022, the Italian government declared a state of emergency in five regions due to the intense water crisis, which coincided with one of the most severe droughts experienced in the last 70 years by the Italian territory. The 652 km-long Po River is the main and longest Italian river and has suffered greatly from the lack of water in its surroundings. This study aims to detect the changes that occurred in the Po River watershed by means of multispectral images (pre- and post-water crisis) obtained by the Sentinel-2 satellite. A methodology different from conventional ones is implemented, which highlights changes by the analysis of images acquired before and after the water crisis. The method is compared to conventional techniques that use subtraction of indexes for the detection of changes. The results obtained here are promising, as the proposed method is a fast and effective approach to mapping the effects of water crisis, besides potentiating the application of the methodology in other areas.